DYNAMICS OF SOME INDICATORS OF SHEEP BLOOD - Elmurad Abdigulomovich Mukhtarov; Dilmurodov Nasriddin Bobokulovich; Bobonazarov Eshmakhamad Ishkuvvatovich (Journal of new century innovations, 2022)
Summary. In the physiological stages of postnatal ontogeny of sheep in different natural conditions, serum albumin and glucose show specific dynamics of changes in relation to living conditions. The changes in the blood of sheep were mainly returned at 6 months and 60 months of posnotol ontogenesis at the highest rate.